Institutional Leadership Commitment and Eradication of Mental Illness Stigmatization among Students of Kenya Medical Training College - Maina J. Kamau; Kenneth Goga Riany (Britain International for Academic Research (BIAR) Publisher, 2023)
Leadership is the main driver of organizational behavior and how people relate in an organization. Through the commitment of institutional leaders to a given culture and way of doing things, the entire organization community is possible to follow the direction the leaders shows. While mental illness has been a major threat to the stability of modern society, the focus has mainly been drawn on treatment, while other affecting factors such as stigmatization not being given the adequate attention. Stigmatization of mentally ill persons is a behavior that requires intensive management by the organizational leaders for it to be contained. Leaders influence behavior, thus their commitment to eradicate mental illness stigmatization would be fundamental in curbing mental illness stigmatization. With inadequate literature on the role played by leadership commitment in curbing mental illness stigmatization, this study seeks to assess the role of institutional leadership on mental illness stigmatization. The study used a descriptive research approach and a questionnaire to collect data from 384 students drawn from a population of 51045 students at the college. The data was analysed using descriptive and inferential statistics through SPSS. The findings revealed that the commitment of institutional leadership in curbing mental illness stigmatization was essential in reducing stigmatization of mentally ill persons. The study concluded that through the commitment of leaders by training and creating awareness was significant in curbing mental illness stigmatization. It is recommended that the institutional leaders have a duty to play in curbing mental illness stigmatization through creation of awareness, training of the students and providing psychosocial support to mentally-ill persons.